Knowledge and Practice Regarding Newborn Care among Postnatal Mother in Selected Community, Bhaktapur - Dangol, Anamika; Shrestha, Ruja; Bhandari, Bhawana; Yakha, Bhim Maya; Pandey, Sita (Journal of Advanced Academic Research, 2023)
Newborn care is a set of comprehensive recommendations designed by World Health Organization (WHO) to improve health of the Newborn through intervention before conception, during pregnancy, soon after birth and in postnatal period. It includes Thermoregulations, Clean delivery, Cord care, Eye care, Newborn feeding, Newborn danger sign, Kangaroo mother care, etc. Objectives: To assess the knowledge and Practice Regarding Newborn care at home among postnatal mother in selected Community Ward no.5. Methods: A descriptive cross sectional study design was conducted among 50 postnatal mothers to gather information on the Knowledge and Practices regarding Newborn care at home among Postnatal Mother in Selected Community Ward no.5, Madhyapur, Thimi. Non-probability purposive sampling techniques was used in this study. A Likert scale was prepared. Data was analyzed by using SPSS (Statistical Package of Social Science Software) Version 20 and various tests frequency and percentage and the findings were presented in tables. Results: This study depicts that, 48(96%) had adequate knowledge regarding Newborn care whereas 2(4%) had inadequate knowledge regarding Newborn Care. Thus, 50(100%) of respondents had good practice regarding Newborn Care. Conclusion: The study shows, postnatal mother had adequate knowledge and good practices regarding thermoregulation, eye care, newborn feeding, newborn danger sign, kangaroo mother care and poor awareness in cord care. While comparing knowledge with practice regarding newborn care, practice looks better in many areas.